2006
DOI: 10.3126/jiaas.v27i0.697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Growth Regulators on Growth, Yield and Quality of Chilli (<i>Capsicum annuum</i> L.) at Rampur, Chitwan

Abstract: The present investigation was carried out in the plain areas of Chitwan to determine the promising plant growth regulators (PGR) promoting growth and yield of chilli cultivars Jwala and Suryamukhi during wintersummer season of 2003/2004. Suryamukhi ranked superior to Jwala for most of the yield attributing characters, whereas Jwala was better in vegetative characters than Suryamukhi. Among PGRs, 2,4-D at 2 ppm was better for fruit set, number of fruits per plant, fruit length, number of seeds per fruit, seed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 2 publications
8
22
0
4
Order By: Relevance
“…As gibberellic acid plays a major role in regulating assimilation and supply to developing sink (Taiz and Zieger, 2002), this treatment favoured the production of maximum number of fruits. A significant increase in fruit length and fruit diameter obtained may be attributed due to nature of auxins (NAA) to stimulate cell division, cell elongation and membrane permeability to water uptake (Chaudhary et al, 2006). Gibberellins are involved in cell division and cell elongation.…”
Section: Effect Of Plant Growth Regulators On Yield and Yield Contribmentioning
confidence: 99%
“…As gibberellic acid plays a major role in regulating assimilation and supply to developing sink (Taiz and Zieger, 2002), this treatment favoured the production of maximum number of fruits. A significant increase in fruit length and fruit diameter obtained may be attributed due to nature of auxins (NAA) to stimulate cell division, cell elongation and membrane permeability to water uptake (Chaudhary et al, 2006). Gibberellins are involved in cell division and cell elongation.…”
Section: Effect Of Plant Growth Regulators On Yield and Yield Contribmentioning
confidence: 99%
“…There were recorded the highest values regarding the number of umbels, fruits per umbel, 100 seed weight, and seed yield, when the TRIA was applied together with GA 3 to coriander crop ) Naeem et al (2009Naeem et al ( , 2010 reported a favorable effect of TRIA on the yield and yield attributes (number of pods and seed yield per plant) of hyacinth bean and coffee senna; the highest values were recorded when the TRIA was applied at a 10 Á6 M concentration. Ivanov and Angelov (1997), Borowski et al (2000), Kumaravelu et al (2000), Chaudhary et al (2006), Sharma et al (2006), and Nogalska et al (2008) reported the significant effect of TRIA on the yield and yield attributes of pea, tomato, green gram, water chestnut, tomato, and soybean, respectively. A significant improvement in fruit-yield of tomato (Khan et al 2006 and crude opium-yield, and seed yield of opium (Khan et al 2007) has also been reported as a result of TRIA application carried out alone or in combination with GA 3 .…”
Section: Yield and Quality Attributesmentioning
confidence: 99%
“…Foliar spray of TRIA increased the dry weight of rice seedlings grown in nutrient medium and that of the plants of corn, barley, and tomato . The growth promoting effects of TRIA on various attributes, especially on plant height, fresh and dry weights, leaf-area and root nodulation, have been explored in various medicinal crops by various researchers (Srivastava and Sharma 1990;Misra and Srivastava 1991;Shukla et al 1992;Muthuchelian et al 2003;Giridhar et al 2005;Chaudhary et al 2006). TRIA improved fresh and dry weights, leaf area, and the number and dry weight of nodules in case of hyacinth bean (Lablab purpureus L.) (Naeem and Khan 2005;Naeem et al 2010).…”
Section: Growth Attributesmentioning
confidence: 99%
“…Similarly, Sutedja (1993) has been successful in increasing the growth of short cuttings vanilla (Vanilla planifolia) through the increase in leaf area and net assimilation rate at a concentration of 0,1 ml/L triacontanol. When compared with other growth regulator, triacontanol in very small amounts can effectively improve the process of growth and production on various types of plants, including on the plant of Arachis hypogaea L. (Verma et al, 2009), Capsicum annuum L. plants (Chaudhary et al, 2006), Solanum melongena L.…”
Section: Introductionmentioning
confidence: 99%